Induction of pluripotent stem cells by reprogramming human ocular fibroblasts under xeno-free conditions - Xiong,Yunfan (2018)
ABSTRACT Purposes: To develop an efficient and xeno-free standard eye-derived induced pluripotent stem cell reprogramming protocol for use during induced pluripotent stem cell-based cell therapies in treating retinal degenerative diseases and to compare the relative effectiveness of both animal- and non-animal-derived culture systems in the generation of induced pluripotent stem cells. Methods: Primary cultured human pterygium fibroblasts and human Tenon’s capsule fibroblasts were induced to induced pluripotent stem cells using a non-integrated virus under two xeno-free systems; as part of this study, a traditional non-xeno-free reprogramming system was also assessed. Induced pluripotent stem cell clones were selected and counted by live staining. Reprogramming efficiencies were evaluated between the fibroblasts and among different culture systems. In a series of experiments, such as PCR and immunofluorescence staining, the induced pluripotent stem cells were characterized. Results: Human pterygium fibroblast- and human Tenon’s capsule fibroblast-derived induced pluripotent stem cells were successfully established using different reprogramming systems, under which they exhibited properties of induced pluripotent stem cells. Reprogramming efficiencies of induced pluripotent stem cells using the cell therapy system, the traditional system, and the E6/E8 system were 0.014%, 0.028%, and 0.001%, respectively, and those of human pterygium fibroblast- and human Tenon’s capsule fibroblast-derived induced pluripotent stem cells-using the aforementioned systems-were 0.018% and 0.017%, respectively. Conclusions: Sendai virus facilitates induced pluripotent stem cell reprogramming of ocular fibroblasts-both human pterygium and human Tenon’s capsule fibroblasts being safe and efficient for induced pluripotent stem cell reprogramming. Although the reprogramming efficiencies of ocular-derived induced pluripotent stem cells under xeno-free conditions were not superior to those observed using the traditional reprogramming system, the cell therapy system reprogramming system is a good option when induced pluripotent stem cells are to be induced under xeno-free conditions.